2003
DOI: 10.1046/j.1471-4159.2003.01955.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological regulation of Munc18/nSec1 phosphorylation on serine‐313

Abstract: Increased protein phosphorylation enhances exocytosis in most secretory cell types, including neurones. However, the molecular mechanisms by which this occurs and the specific protein targets remain unclear. Munc18-1/nSec1 is essential for exocytosis in neurones, and is known to be phosphorylated by protein kinase C (PKC) in vitro at Ser-313. This phosphorylation has been shown to decrease its affinity for syntaxin, and to alter the kinetics of exocytosis in chromaffin cells. However, there are no data on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 48 publications
5
44
0
Order By: Relevance
“…As discussed above, the Y337L Munc18-1 mutation affects exocytotic release kinetics, consistent with an effect on the late stages of the membrane fusion process. Interestingly, S313 in Munc18-1, which is very close to Y337 in domain 3a, has been shown to be regulated physiologically by PKC phosphorylation, resulting in altered exocytotic release kinetics (Barclay et al 2003;Craig et al 2003). Taken together, it seems likely that domain 3a is a functionally important region in SM proteins that is involved in the membrane fusion process.…”
Section: Discussionmentioning
confidence: 97%
“…As discussed above, the Y337L Munc18-1 mutation affects exocytotic release kinetics, consistent with an effect on the late stages of the membrane fusion process. Interestingly, S313 in Munc18-1, which is very close to Y337 in domain 3a, has been shown to be regulated physiologically by PKC phosphorylation, resulting in altered exocytotic release kinetics (Barclay et al 2003;Craig et al 2003). Taken together, it seems likely that domain 3a is a functionally important region in SM proteins that is involved in the membrane fusion process.…”
Section: Discussionmentioning
confidence: 97%
“…The R39C mutation or a phosphomimetic mutant (S306E,S313E) of Munc18-1 reduced the affinity of binding to syntaxin, and in amperometric measurements of release their expression resulted in reduced quantal size (possibly because of a switch to kiss and run exocytosis) and faster release kinetics. These effects may reflect physiological regulation of exocytosis via protein kinase C activation (29,51). The effect of these Munc18-1 mutants in transfected cells could potentially arise from more ready release of bound syntaxin into the open conformation or alternatively from syntaxin-independent effects of released Munc18-1 mutants that are not bound to syntaxin.…”
Section: Effect Of Overexpression Of Syntaxin 1a or Its Cytosolic Dommentioning
confidence: 99%
“…In many cell types, Munc-18 is crucial for the docking and priming of secretory granules, as well as for actual fusion with the plasma membrane [30]. It has been demonstrated that Munc-18 is phosphorylated by PKC in response to phorbol ester treatment [31,32].…”
Section: Introductionmentioning
confidence: 99%